2013
DOI: 10.1111/and.12105
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lipid metabolism down-regulates adenosine triphosphate synthase β-subunit protein expression in corpus cavernosum smooth musclein vitroandin vivo

Abstract: Metabolic syndrome is closely related to erectile dysfunction (ED), and hyperlipidaemia is considered a major risk factor for ED. Adenosine triphosphate (ATP) synthase is believed to play an important role in metabolic syndrome; it has been hypothesised that ATP synthase contributes to ED development. We have verified this hypothesis using primary cultured human corpus cavernosum smooth muscle (HCCSM) cells treated with excessive free fat acid (FFA) and a high-fat diet (HFD) mouse model. Our results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It has been consistently shown that the prevalence of ED is significantly correlated with age and vascular risk factors including atherosclerosis, hypertension, hypercholesterolaemia, diabetes and lifestyle issues (Musicki et al., ). ED is known as one of the symptoms of cardiovascular disease and significantly associated with metabolic syndrome (metS) (Chaudhary, Shamsi, Tan, Chen, & Xing, ; Liu et al., ). The metS is a progressive disease, which is manifested by combination of hypertension, abdominal obesity, insulin resistance, hyperglycaemia, dyslipidaemia, glucose intolerance and at various clinical conditions associated with type 2 diabetes and vascular pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been consistently shown that the prevalence of ED is significantly correlated with age and vascular risk factors including atherosclerosis, hypertension, hypercholesterolaemia, diabetes and lifestyle issues (Musicki et al., ). ED is known as one of the symptoms of cardiovascular disease and significantly associated with metabolic syndrome (metS) (Chaudhary, Shamsi, Tan, Chen, & Xing, ; Liu et al., ). The metS is a progressive disease, which is manifested by combination of hypertension, abdominal obesity, insulin resistance, hyperglycaemia, dyslipidaemia, glucose intolerance and at various clinical conditions associated with type 2 diabetes and vascular pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, hyperglycemia has been demonstrated to impair mitochondrial function and inhibit ATP synthase activity, leading to reduced levels of ATP production (28). Liu et al (5) showed that high glucose resulted in abnormal lipid metabolism, in turn leading to a decrease in ATP synthase expression through the Akt phosphorylation pathway in CCSMCs, suggesting that ATP synthase is essential for CCSMC function in hyperglycemia. In the present study, continuous exposure to high glucose reduced the expression of the F 1 -ATP synthase protein in both rat CCSMCs and smooth muscle tissues from the corpus cavernosum in diabetic rats.…”
Section: Discussionmentioning
confidence: 98%
“…Corpus cavernosum smooth muscle function involves a plethora of complex intracellular events and extracellular signals (3,4). Since smooth muscle cell (SMC) function depends heavily on mitochondrial activity a strong association exists between mitochondrial dysfunction and dysfunction in the corpus cavernosum smooth muscle (5). In particular, long-term hyperglycemia has been reported to reduce mitochondrial biogenesis, increase the ADP/ATP ratio, induce ultra-structural changes and markedly increase the production of reactive oxygen species (ROS) (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for ED include age, obesity, smoking, depression, and metabolic disorders ( 3 ), which are more common in middle-aged and elderly men with diabetes ( 4 , 5 ). Long-term hyperglycemia in diabetic patients induces the production of large amounts of reactive oxygen species that impair mitochondrial and smooth muscle function in the corpus cavernosum, which leads to ED ( 6 , 7 ). In different regions of the world, the prevalence of diabetes mellitus-induced erectile dysfunction (DMED) ranges from 35.8% to 86.1% ( 8 ), and 12% of diabetic patients have ED as the first symptom ( 9 ).…”
Section: Introductionmentioning
confidence: 99%